Listening to the Transition: Adolescent to Adult. Issue 1 (31st March 2017) - Chused, Judith Fingert
ABSTRACT: The process of disidentification from parental figures that begins in adolescence often results in considerable confusion of thought and emotions. Difficulty with this developmental step is a major factor in the young adult's need for analytic treatment. Patients unable to complete the second stage of separation-individuation come to treatment either still fighting with their parents or relying too heavily on their direction. During the course of an analysis of a young adult, the analyst is confronted with a patient alternately complaining about his or her parents or idealizing them, speaking as if their words and desires could not be questioned. A major task for the analyst will be to discern to whom the patient listens to inside his or her head: the people, past and present, who live as images with demands and needs; the people to whom the patient speaks when he or she speaks to the analyst; and the people for whom the patient is still performing. The analysis of a young man is presented to illustrate this analytic challenge.